Aksara Cacarakan pada Arsip Akta Jual Beli Tanah Milik Bupati Sumedang Pangeran Aria Soeria Atmadja - Fitriatno, Ery Giana; Ma'mun, Titin Nurhayati; Ikhwan, Ikhwan (Jumantara: Jurnal Manuskrip Nusantara, 2023)
This article discusses the archives of the land purchase and sale act belonging to Bupati Sumedang Pangeran Aria Soeria Atmadja. The land purchase and sale act was written on May 3, 1915, in Conggeang, Sumedang. The archive is part of the collection of the Library of the Yayasan Nadzir Wakaf Pangeran Sumedang. It was written using the Cacarakan script in the Sundanese language. The writing style of the Cacarakan script contained in the archives is unique, with some characters having two different writing models. In addition, there are peculiarities and uniqueness in the archives that can only be found in the land purchase and sale act archive. To identify the characters and uncover the uniqueness contained in the archive, this research will apply the method of philological research with a manuscript study (codicology) approach. By using the codicology method, the consistency of writing the Cacarakan script, uniqueness, and peculiarities contained in the 1915 land purchase and sale act belonging to Bupati Sumedang Pangeran Aria Soeria Atmadja can be revealed.